Ques for Islam - "Khwaja, Jamal" (Bombay, 1977)
Quest for Islam is a systematic exposition of Islam in the light of contemporary knowledge by a practicing Muslim. A seminal work, it successfully resolves intellectual difficulties created in traditional interpretations by new knowledge. Among other things it organically integrates core Islamic values with the requirements of plural societies and secular democracies. It thus adds a fresh dimension of value to the Islamic thought-cum-value system. It will appeal greatly to Muslim intellectuals perplexed by the assault of modernity on traditional values and institutions. The Author argues that we must always be alive to the need for evolutionary growth and judicious innovation. In the global village, knowledge of how 'they' live is commonplace and comparisons are inevitably made. Consequently young Muslims have more questions than ever before for their elders. The "do as you are told", and the "shut up and conform" responses are patently inappropriate. The quest for an 'Islam For Our Times' is, therefore a road that all thinking Muslims must travel with humility and abundant faith in the merciful guidance of God.
Keywords: Religion